PENGARUH PEMBERIAN PUPUK NPK TERHADAP PERTUMBUHAN RUMPUT SETARIA (Setariasphacelata) PADA TANAH BEKAS TAMBANG BATU BARA DI KECAMATAN RANTAU PANDAN KABUPATEN BUNGO - Hiquita julianur resmana; supriyono supriyono; bela putra (Universitas Muara Bungo, 2019)
This research was carried out in Sapta Mulia Village, Rimbo Bujang Sub District, Tebo Regency by using the land of PT. SAS Coal Mine which was established in 2013 with a land area of 5 hectares. The research was carried out in July 2018 - August 2018, the purpose of this study was to obtain the use of NPK fertilizer more efficiently and effectively for setaria grass. This research is an experimental study that was designed based on a completely randomized design (CRD), with 5 treatments and 4 replications with NPK fertilizer on former coal soil as for the treatment (P0). Without Giving NPK Fertilizer 0 ton / ha, (P1): NPK Fertilizer 175 kg / ha = 3.6 gram / polybag, (P2): NPK Fertilizer 350 kg / ha = 7.2 gram / polybag, (P3): NPK 525 kg fertilizer / ha = 10.8 gram / polybag, (P4): NPK fertilizer 700 kg / ha = 14.4 grams / polybag. Parameters observed were plant height (cm), number of leaves (strands), leaf area (cm ), plant fresh weight (Kg), yield of setaria grass plants (tons / ha). The treatment of P3 showed the best results of setaria grass plants on plant height (cm) and leaf area (cm ), on the number of leaves (strands), fresh weight of planting (gr), the highest yield of plants (ton / ha) in P4 treatment. Treatment of P4 NPK Fertilizer 700 kg / ha = 14.4 gram / polybag which gives the best results then followed by treatment P0, P1, P2 and P3.